2022
DOI: 10.1177/21582440221085016
|View full text |Cite
|
Sign up to set email alerts
|

Distance Learning and Assessment During the COVID-19 Pandemic—Perspectives of Polish Medical and Healthcare Students

Abstract: The abrupt transition from the traditional model of medical education to online learning caused by the COVID-19 pandemic led to unprecedented changes in the education of future healthcare professionals. This study aimed to evaluate the opinions of Polish healthcare students on the changes introduced due to the COVID-19 pandemic and propose recommendations for improvement. Data were collected from June to July 2020 using an online questionnaire. The results demonstrate that students were generally satisfied wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…However, it should be emphasized that students must also have the appropriate connection and equipment. The problems with Internet connections were also often indicated in the studies performed in the UK [5] and Poland [22]. In our study, 16.8% of respondents cited inadequate Internet access as a restriction to the educational process.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…However, it should be emphasized that students must also have the appropriate connection and equipment. The problems with Internet connections were also often indicated in the studies performed in the UK [5] and Poland [22]. In our study, 16.8% of respondents cited inadequate Internet access as a restriction to the educational process.…”
Section: Discussionsupporting
confidence: 63%
“…The main restriction for the quality of education process respondents indicated the quality of the content and available materials, the lack of contact with the lecturer, and adequate Internet access. Similar problems were indicated by medical students in another Polish study [22], however, a part of the students considered positive aspects of e-learning as indicating bigger student-friendliness and unlimited attention from teachers [22]. This indicated that lecturers' involvement is a very important part of the quality of e-learning.…”
Section: Discussionsupporting
confidence: 51%
“…For example, in the United States, the number of job offers for nurses was estimated to be higher than for any other occupation by 2022 [ 25 ]. Though medical universities have implemented online solutions [ 6 ], this education form does not enable students to acquire all the qualifications necessary to practice their profession. At the same time, as mentioned above, we observed that medical universities became strongly involved in the fight against the pandemic at the institutional level, enabling screening, creating temporary hospitals, and organizing volunteer support.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the case of medical education, online learning may not necessarily be an optimal solution [ 4 , 5 ]. Despite its many advantages, great potential, and the variety of available e-learning tools, the limitations of online learning should also be considered, including difficulties in learning practical skills, limited contact between teachers and students, and the risk of lowering the quality of learning and assessment [ 6 ]. There is also a risk of failing to meet the basic principles of constructive alignment, which assume the need for consistency between learning outcomes and learning activities [ 7 ] as a result of the incorrect implementation of online learning in areas such as practical and clinical reasoning or communication skills learning.…”
Section: Introductionmentioning
confidence: 99%
“…It should be kept in mind that e-learning, despite its many advantages, also has its limitations and may cause some difficulties for instructional designers, for example, in building interactions between course participants. In such a case, to create a space for the exchange of experiences and opinions, it is worth setting up a set of quick contact paths with the use of, for instance, social media or built-in solutions in e-learning platforms (e.g., a forum) [ 64 ]. Participants should be given a chance to implement the solutions in practice and encouraged to share their thoughts with the facilitators and other participants.…”
Section: Discussionmentioning
confidence: 99%